Relationship Characteristics of Pregnant Women with Premature Rupture Ketubban - Kasum, Nurhadimah (Hasanuddin Medan, 2023)
The World Health Organization (WHO) predicts that between 2010-2014, there would be 300-400 maternal deaths per 100,000 live births, with hemorrhage accounting for 28% of these deaths and preterm membrane rupture for 20%. Premature membrane rupture is a complication of preterm pregnancy that significantly increases the risk of perinatal death and premature birth. The purpose of this study is to ascertain the association between the prevalence of early membrane rupture at RSU Haji Medan and the age and parity of pregnant women. This study adopted a cross sectional methodology and an analytical survey research design. All pregnant women who suffered early membrane rupture and other problems made up the population of this study, and a total of 71 pregnant women were sampled. Data from medical records as a source It was done using both univariate and bivariate analysis. According to the study's findings, there were 35 pregnant women, of whom 13 were under 20 years old (18.3%), 11 were between 20-35 years old (15.5%), and 11 > 35 years old (15.5%) when their membranes ruptured prematurely. With a 95% confidence interval, the values are = 0.005 and P = 0.046. Consequently, the findings indicate that there is a correlation between age and the frequency of premature membrane rupture, with ? = 0.005 and P = 0.022. The findings thus indicate a connection between parity and the frequency of early membrane rupture at RSU Haji Medan.